COMPARATIVE ANALYSIS OF THE STATE AND NATIONAL SECURITY ESSENCE - KRUPA, Oleksandr (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The problems of state security ensuring have been in the field of scientific community and authority view for many centuries, and the range of these studies is being expanded and supplemented with new problems every time due to the development of societies and international relations. However, the lack of systematic approach regarding the conceptual apparatus in this area, first of all, in the Ukrainian scientific discourse, leads to problems not only in matters of delineating the theoretical and methodological basis, but also in the practical plane of effective management of state security. Since the existing works in Ukraine are based mainly on the foundations of the Ukrainian etymological and historical context, the problem of distorted perception of their content arises, which requires additional research. The purpose of the study is to highlight the diverse approaches to the concepts of state and national security in the Ukrainian- and English-speaking scientific discourse and, based on them, to carry out a comparative analysis of the studied terms. In the article studied the modern works of Ukrainian scientists on the issues of distinguishing substantive aspects and the expediency of differentiation between the concepts of state and national security. Characterized the modern security theories founders’ views. Carried out an analysis of the frequency of use of the concepts "national security", "state security" and "nation-state security", and substantiated the opinion regarding their synonymous connection. Conducted a comparative analysis of views in Ukrainian and English-language scientific works on the essence of the categories "state security " and "national security" and characterized the key critical remarks in the Ukrainian discourse regarding the expediency of their application.
Keywords: security; state security; national security; essence; characteristics; comparative analysis